Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1017/s1751731114000160
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting cellularity on fat deposition in the subcutaneous adipose tissue and longissimus lumborum muscle from lean and fat pigs under dietary protein reduction

Abstract: The production of pork with high amounts of intramuscular fat (IMF) without an increase in subcutaneous fat is highly desirable for the pig industry and consumers. Herein, we question the impact of dietary protein reduction (18% v. 13%) on fat deposition in the subcutaneous adipose tissue (SAT) and longissimus lumborum (LL) muscle using genetically diverse pigs for body fatness (lean v. fat). A clear effect of genotype was observed on plasma insulin (P = 0.004) and leptin (P < 0.001), as well as on backfat thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(41 reference statements)
1
6
0
1
Order By: Relevance
“…Although the authors showed a slight increase in IMF content (from 1.78% to 2.06%) in Alentejana purebred pigs, this is still a small amount. This was clearly confirmed by studies by Lopez et al [ 52 ], who reported a significantly higher intramuscular fat content with a 5% reduction in protein levels in the diet ( p < 0.003). According to research by Olivares et al [ 53 ], the addition of high levels of vitamin A (dVitA; 100,000 IU) to the diet of Duroc boars resulted in a 20% increase in the IMF of their offspring.…”
Section: Resultssupporting
confidence: 78%
“…Although the authors showed a slight increase in IMF content (from 1.78% to 2.06%) in Alentejana purebred pigs, this is still a small amount. This was clearly confirmed by studies by Lopez et al [ 52 ], who reported a significantly higher intramuscular fat content with a 5% reduction in protein levels in the diet ( p < 0.003). According to research by Olivares et al [ 53 ], the addition of high levels of vitamin A (dVitA; 100,000 IU) to the diet of Duroc boars resulted in a 20% increase in the IMF of their offspring.…”
Section: Resultssupporting
confidence: 78%
“…The size of the IMF adipocytes in the BF muscle was studied in the growing Iberian and Duroc animals, with larger adipocytes being observed in the Iberian breed than in the Duroc breed (86.3 microns versus 70.10 microns, respectively; p -value < 0.0001). Although there are histological studies comparing the adipocytes of fat and lean breeds [ 40 ], to the best of our knowledge, this is the first study that compares, at the histological level, the IMF adipocytes between Iberian and Duroc pure growing pigs. The micrographs of Iberian and Duroc intramuscular adipocytes are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Economically important pig breeds such as the Large White and Duroc have thin subcutaneous fat, while Tibetan pigs have high fat-deposition levels and delicious and nutritious meat ( Gan et al, 2019 ; Shen et al, 2014 ). Differences in morphology and lipid-regulated genes also exist between breeds and adipose tissue types ( Lopes et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%